ENHACING CRITICAL THINGKING THROUGH PROBLEM BASED LEARNING IN ISLAMIC EDUCATION - Ahmad Sukardi; Kholilurrohman Kholilurrohman; Fathi Hidayah; Bannaga Taha Elzubair Hussen (Nurul Jadid University, Paiton Probolinggo, East Java, 2024)
This research focused on evaluating the effectiveness of Problem-Based Learning (PBL) within the context of Islamic religious education at High School. A qualitative case study approach was used, with data collected from in-depth interviews with 20 participants, participatory observations, and analysis of curriculum documents. Data were collected through a series of in-depth interviews, participatory observations, and analysis of the curriculum documents used at the school. The findings indicate that PBL supports students not only in understanding theoretical religious concepts but also in applying these values practically in their daily lives. Moreover, this method has proven to enhance students' learning motivation and analytical abilities. This study offered concrete guidelines for integrating PBL into Islamic education curricula and suggests further research across different schools to assess generalizability. The implications of this study were highly relevant for the development of a more innovative and responsive curriculum to modern educational needs.